2009
DOI: 10.1016/j.ccr.2009.02.023
|View full text |Cite
|
Sign up to set email alerts
|

ZNF423 Is Critically Required for Retinoic Acid-Induced Differentiation and Is a Marker of Neuroblastoma Outcome

Abstract: SUMMARY Retinoids play key roles in differentiation, growth arrest and apoptosis and are increasingly used in the clinic for the treatment of a variety of cancers, including neuroblastoma. Using a large-scale RNA interference-based genetic screen we identify ZNF423 (also known as Ebfaz, OAZ or Zfp423) as a component critically required for retinoic acid (RA)-induced differentiation. ZNF423 associates with the RARα/RXRα nuclear receptor complex and is essential for transactivation in response to retinoids. Down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 45 publications
3
137
0
1
Order By: Relevance
“…4D). Other studies have shown that loss of activation of RA target genes blocks RA-induced differentiation (20,21). It is therefore likely that the loss of activation of a subset of RA target genes contributes to RA resistance in MAML3-overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4D). Other studies have shown that loss of activation of RA target genes blocks RA-induced differentiation (20,21). It is therefore likely that the loss of activation of a subset of RA target genes contributes to RA resistance in MAML3-overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using loss-offunction genetic screens Huang and colleagues showed that knockdown of the zinc finger protein ZNF423 leads to the loss of activation of RA target genes. ZNF423 binds to the RAR/RXR complex and acts as a transcriptional coactivator (20). In another study, loss of the tumor suppressor NF1 was shown to determine responsiveness to RA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain insights into the regulation of cell proliferation by Ras proteins beyond the Raf/Mek/Erk cascade and to identify key elements that connect Ras signaling with the cell cycle machinery, we submitted mouse embryonic fibroblasts (MEFs) lacking all of the Ras proteins (Rasless cells) to an unbiased shRNA library "barcode" screen (10,11) (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…1A). K-Raslox cells were transfected with the shRNA library and scored for cells capable of proliferating in the absence of Ras proteins (10,11) (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%